Energy recovery evaluation and temperature field research of underground coal gasification under different oxygen concentrations. (1st December 2022) - Su, Fa-qiang; Zhang, Tao; Wu, Jun-bo; Deng, Qi-chao; Hamanaka, Akihiro; Yu, Yi-he; Dai, Meng-jia; He, Xiao-long; Yang, Jun-nan
Highlights: The amount of the reacted carbon was estimated with the volume of oxygen injected. The energy recovery rate to evaluate the gasification efficiency was proposed. A gasification temperature evaluation model was suggested. Abstract: In this paper, UCG simulation experiments were carried out on selected coal samples to study the effects of the gasification agent ratio on the product gas composition and calorific value under different oxygen concentrations. Moreover, an energy recovery evaluation method based on stoichiometric theory was established based on the carbon (C) balance in the generated gas content, and the energy recovery rate and coal consumption of the underground gasification process were evaluated. Based on the composition of the produced gas and the thermodynamic law of conservation, an evaluation model of the underground coal gasification temperature field was established. The gasification chamber temperature in each stage was evaluated by calculating the reaction heat and sensible heat. The experimental and research results showed that when the volume fraction of oxygen in a gasification agent was in the range 40–70 % and the calorific value of the produced gas increased from 10.48 MJ/m 3 to 12.48 MJ/m 3 . The calorific value of the produced gas increased with an increasing oxygen concentration. Furthermore, the energy recovery rate increased from 69.63 % to 83.88 %, indicating that the gasification efficiency of the UCG experiment can be significantly improved with an increasing oxygen concentration. The error between the theoretical value of the coal consumption and the actual monitoring value was within 10 %, which effectively evaluates the coal consumption in the gasification process. The theoretical calculation temperature was consistent with the experimental monitoring temperature results, and the reaction heat was found to also be linearly correlated with the gasification temperature. Therefore, this method can effectively determine the gasification chamber temperature. These monitoring and evaluation methods are expected to guide the analysis of subsurface field experiments.